Organic conductive agent, preparation method of low-silver content low-temperature curing conductive paste and electronic component
By using organic conductive agents with nano-short fiber structures in low-temperature electronic pastes to build a three-dimensional conductive network, the problems of high silver powder content and difficult performance improvement in existing low-temperature electronic pastes are solved, and the conductive and mechanical properties are significantly improved and the use of silver powder is reduced.
Patent Information
- Application Number
- CN202310161314.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-02-24
AI Technical Summary
The content of silver powder conductive agent in existing low-temperature electronic pastes is high, which leads to expensive costs, and at the same time, the printing and curing reaction is complex, making it difficult to improve performance.
A mixed solution is arranged using doped acid and template agent, monomer raw materials and oxidizing agent are added, and the nano-staple fiber structure is obtained after stirring and standing reaction, and the organic conductive agent with nano-staple fiber structure is added to the silver paste binder solution. After pre-rolling and vacuum stirring and defoaming, a low-temperature cured conductive paste is prepared.
By constructing a three-dimensional conductive network structure, the conductivity and mechanical properties of low-temperature cured conductive paste are significantly improved, the use of silver powder is reduced, and the cost is reduced.
Smart Images

Figure CN116120546B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive pastes, and in particular relates to an organic conductive agent, a preparation method of a low-silver content, low-temperature curing conductive paste, and an electronic component. Background Art
[0002] Electronic paste is the basic material for manufacturing thick film components. It is a paste made of solid powder and organic solvent mixed evenly by three rollers. According to the different sintering temperatures, it can be divided into high temperature, medium temperature and low temperature drying electronic paste.
[0003] Low-temperature electronic paste, also known as low-temperature curing electronic paste, has developed into a key material in applications in the microelectronics field such as front silver of photovoltaic devices, chip packaging and connection, 5G communication base stations, advanced printed electronics, and flexible wearable electronics.
[0004] At present, the content of silver powder conductive agent in low-temperature (i.e. less than 300°C) electronic paste is usually greater than 80%, and the usage is large, resulting in high cost. On the other hand, the printing of low-temperature electronic paste requires the polymer chemical curing reaction to complete the phase transition from viscous flow to solid state, and the preparation technology barrier is high, making it difficult to improve its comprehensive performance. Summary of the invention
[0005] The purpose of the present invention is to provide an organic conductive agent, a preparation method of a low-silver content low-temperature curing conductive paste and an electronic component, reduce the silver powder content in the low-temperature curing conductive paste, and improve the conductive performance of the paste.
[0006] The present invention adopts the following technical scheme: a method for preparing an organic conductive agent, comprising the following steps:
[0007] preparing a first mixed solution using a doping acid and a template agent;
[0008] Adding a monomer raw material to the first mixed solution, and stirring to obtain a second mixed solution; wherein the molar ratio of the monomer raw material to the doping acid is 1:1, and the molar ratio of the template to the monomer raw material is (0.5-1):5;
[0009] Adding an oxidant to the second mixed solution, and standing at 0-5° C. until the reaction is complete to obtain a precipitated product; wherein the molar ratio of the oxidant to the monomer raw material is (1-1.2):1;
[0010] The precipitated product is washed and dried in sequence to obtain an organic conductive agent.
[0011] Furthermore, after obtaining the organic conductive agent, the method further comprises:
[0012] The organic conductive agent is immersed in a concentrated acid solution, and then washed and dried in sequence to obtain an enhanced organic conductive agent; wherein the mass ratio of the organic conductive agent to the concentrated acid solution is (1-6):100.
[0013] Further, adding an oxidant to the second mixed solution comprises:
[0014] The oxidant is uniformly added to the second mixed solution at a rate of 0.8 to 1 mL / min.
[0015] Further, washing and drying the precipitated product in sequence comprises:
[0016] The precipitated product was washed with deionized water, methanol, acetone and ether solvents in sequence.
[0017] Further, the doping acid is at least one of hydrochloric acid and sulfosalicylic acid, and the concentration of the doping acid is 1 to 1.5 mol / L;
[0018] The template agent is methyl orange or polyvinyl pyrrolidone;
[0019] The monomer raw material is aniline or pyrrole;
[0020] The oxidant is ammonium persulfate or ferric chloride;
[0021] The concentrated acid solution is at least one of nitric acid, sulfuric acid and hydrochloric acid;
[0022] Furthermore, the organic conductive agent is at least one of polyaniline and polypyrrole.
[0023] Another technical solution of the present invention is a method for preparing a low-silver content low-temperature curing conductive paste, using the organic conductive agent prepared by the above method, comprising the following steps:
[0024] Adding polyurethane and isocyanate into an organic mixed solvent and fully dissolving them respectively to obtain a polyurethane solution and an isocyanate solution;
[0025] The polyurethane solution and the isocyanate solution are mixed in a predetermined ratio to obtain a silver paste adhesive solution;
[0026] Adding an organic conductive agent into the silver paste adhesive solution and pre-rolling the solution to obtain an organic slurry;
[0027] Adding silver powder to the organic slurry and stirring evenly to obtain a conductive slurry premix; wherein the silver content in the conductive slurry premix is 50wt% to 60wt%;
[0028] Rolling the silver paste premix until the fineness of the silver paste is 3-5 μm; wherein the rolling is a staged rolling method;
[0029] The silver paste after rolling is subjected to vacuum stirring and degassing treatment to obtain a low-silver content, low-temperature curing conductive paste.
[0030] Furthermore, the content of the organic conductive agent in the conductive paste premix is 0.1 wt% to 5.0 wt%.
[0031] Furthermore, the staged rolling method is:
[0032] The front roller distance is reduced from 120μm to 80μm in stages of 20μm, and the roller is pressed 1 to 3 times in each stage;
[0033] The back roller distance is reduced from 140μm to 100μm in stages of 20μm, with 1 to 3 rolls in each stage;
[0034] The front roller gap and the rear roller gap are reduced to 3-5μm in stages from 3 to 20μm, and the rollers are rolled 3 to 5 times in each stage, with the rotation speed of each stage being 100rpm.
[0035] Another technical solution of the present invention: an electronic component, comprising the low-silver content, low-temperature curing conductive paste prepared by the above method.
[0036] The beneficial effects of the present invention are as follows: by adding an organic conductive agent with a nano-short fiber structure into the conductive paste premix, the present invention can enhance the shrinkage and binding ability of the silver powder particles, form microphase separation after curing and shrinkage, construct a three-dimensional network structure, provide good conductive channels, compatibility and binding force, so that the conductive, mechanical and other properties of the low-temperature curing conductive paste are significantly enhanced, and then the amount of silver powder used in the low-temperature curing conductive paste can be greatly reduced, thereby achieving the effect of reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The present invention is a schematic diagram of a preparation process of a method for preparing a low-silver content, low-temperature curing conductive paste according to an embodiment of the present invention;
[0038] Figure 2 The schematic diagrams of scanning electron microscope and transmission electron microscope are schematic diagrams of the organic conductive agent prepared in the embodiment of the present invention;
[0039] Figure 3 is a schematic diagram of a scanning electron microscope of the silver powder used in the embodiment of the present invention;
[0040] Figure 4 This is a schematic diagram of a scanning electron microscope after the low-silver content and low-temperature conductive paste is printed and cured in an embodiment of the present invention;
[0041] Figure 5 The schematic diagram and design diagram of the conductors obtained by printing the low-silver content, low-temperature curing conductive paste in the embodiment of the present invention;
[0042] Figure 6Schematic diagram of a three-dimensional conductive network structure in an embodiment of the present invention. DETAILED DESCRIPTION
[0043] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0044] The invention discloses a method for preparing an organic conductive agent, comprising the following steps: configuring a first mixed solution by using a doping acid and a template agent; the first mixed solution provides acidic reaction conditions and a polymerization soft template for the controllable preparation of the organic conductive agent; adding a monomer raw material to the first mixed solution, stirring to obtain a second mixed solution, acidifying the monomer to become a protonated salt through stirring, and the stirring speed during the reaction is preferably 300-500 rpm; wherein the molar ratio of the monomer raw material to the doping acid is 1:1, and the molar ratio of the template agent to the monomer raw material is (0.5-1):5.
[0045] Slowly add the oxidant to the second mixed solution, and stand at 0-5°C until the reaction is complete, usually for 5-8 hours, to obtain a precipitated product; wherein the molar ratio of the oxidant to the monomer raw material is (1-1.2):1; the precipitated product is washed and dried in turn to obtain an organic conductive agent.
[0046] In the present invention, a hydrophilic and lipophilic template forms a long rod-shaped micelle template in a solution system, protonated aniline is adsorbed on the surface of the template micelle template, and is polymerized and aggregated through chemical oxidation by an oxidant to form a polymer with a short fiber microstructure, and an organic conductive agent is obtained through subsequent washing, enhanced doping and drying.
[0047] In one embodiment, adding the oxidant to the second mixed solution includes: adding the oxidant to the second mixed solution at a uniform speed, with the adding speed being 0.8-1 mL / min.
[0048] In this embodiment, the organic conductive agent with a nano-short fiber structure is prepared by a soft template method and enhanced by doping, which can effectively increase the conductivity of the organic conductive agent, strengthen the shrinkage and binding of the silver powder particles and the organic conductive agent, form microphase separation after solidification and shrinkage, and construct a three-dimensional conductive network structure. The structure is as follows Figure 6 shown.
[0049] Providing good conductive channels, compatibility and convergence force significantly enhances the conductive, mechanical and other properties of the low-temperature curing conductive paste, thereby greatly reducing the amount of silver powder used in the low-temperature curing conductive paste and achieving the effect of reducing costs.
[0050] Specifically, after obtaining the organic conductive agent, the method further includes: immersing the organic conductive agent in a concentrated acid solution. In this embodiment, a 2 mol / L concentrated acid solution is selected, and the immersion time is designed to be 10 to 24 hours. This step can enhance the protonation doping degree, thereby improving the conductive performance.
[0051] Then, washing and vacuum drying are performed in sequence to obtain an organic conductive agent with enhanced acid conductivity; wherein the mass ratio of the organic conductive agent to the concentrated acid solution is (1-6):100.
[0052] In one embodiment, washing and drying the precipitated product in sequence comprises: washing the precipitated product in sequence with deionized water, methanol, acetone and ether solvents. Through the washing process, the reaction byproducts and unreacted substances can be removed, and then vacuum drying at 60° C. for 24 to 36 hours to obtain a powdered organic conductive agent.
[0053] First, the powder product is washed with deionized water until the pH value of the filtrate is 6-7 to remove the free doping acid; then the product is washed with methanol until the filtrate is colorless to remove the template; then the product is washed with acetone and ether until the filtrate becomes clear to remove the soluble oligomers produced by the reaction.
[0054] In an embodiment of the present invention, the doping acid is at least one of hydrochloric acid and sulfosalicylic acid, and the concentration of the doping acid is 1-1.5 mol / L; the template agent is methyl orange or polyvinyl pyrrolidone; the monomer raw material is aniline or pyrrole; the oxidant is ammonium persulfate or ferric chloride; and the concentrated acid solution is at least one of nitric acid, sulfuric acid and hydrochloric acid.
[0055] Based on the above raw materials, the organic conductive agent finally prepared in this embodiment is at least one of polyaniline and polypyrrole.
[0056] The present invention also discloses a method for preparing a low-silver content, low-temperature curing conductive paste, such as Figure 1 As shown, the organic conductive agent prepared by the above method comprises the following steps:
[0057] First, an organic mixed solvent is prepared. Specifically, the organic mixed solvent is prepared from two mixed solutions of 85wt% to 90wt% A and 10wt% to 15wt% B; wherein the A solution is one of dimethyl succinate, dimethyl glutarate and dimethyl adipate; and the B solution is one of 3,5,5-trimethyl-2-cyclohexene-1-one, methyl isobutyl ketone, cyclohexanone and diacetone alcohol.
[0058] Polyurethane and isocyanate are added to an organic mixed solvent, heated at 70-80°C for 2-3 hours, and fully dissolved to obtain a polyurethane solution and an isocyanate solution with a solid content of 15-25%. In this embodiment, the polyurethane is a polyester polyurethane with a molecular weight (Mw) of 80,000-120,000, and the isocyanate is a closed ring polyisocyanate.
[0059] Next, the polyurethane solution and the isocyanate solution are mixed in a predetermined ratio to obtain a silver paste adhesive. In the present embodiment, the mass ratio of the polyurethane solution to the isocyanate solution is 8:1. If too much isocyanate is added, the paste will be too hard. Therefore, the predetermined ratio is determined based on the mechanical properties, aging resistance, curing time, construction process, etc. of the final paste, and can be adjusted according to demand.
[0060] The organic conductive agent is added to the silver paste adhesive solution, and pre-rolling is performed to obtain an organic slurry. Specifically, a three-axis rolling mill is used for pre-rolling to obtain a uniform and viscous organic slurry.
[0061] Silver powder is added to the organic slurry. The scanning electron microscope photo of the silver powder is as follows: Figure 3 As shown, after stirring evenly, a conductive paste premix is obtained; wherein the silver content in the conductive paste premix is 50wt% to 60wt%; the silver paste premix is rolled until the silver paste fineness is 3-5μm; wherein the rolling is a staged rolling method. The content of organic conductive agent in the conductive paste premix is 0.1wt% to 5.0wt%,
[0062] Finally, the silver paste after rolling is subjected to vacuum stirring and degassing treatment to obtain a low-silver content low-temperature curing conductive paste. Degassing and stirring treatment parameters: 2500-3000 rpm rotation speed, stirring for 5-10 minutes, vacuum degree -98Kpa.
[0063] First, an organic conductive agent is added to the silver paste adhesive solution, and the organic conductive agent and the adhesive solution are fully compatible through roller rolling, which is conducive to the stretching and uniform dispersion of the short fiber-shaped organic conductive agent in the adhesive solution. The silver powder added thereafter can be intercalated with the organic conductive agent after roller rolling to arrange in an orderly manner to construct a three-dimensional network structure, forming a good conductive channel, which is conducive to charge transfer and improvement of conductive performance.
[0064] The present invention adds an organic conductive agent with a nano-short fiber structure into the conductive paste premix, thereby enhancing the shrinkage and binding ability of the silver powder particles, forming microphase separation after curing and shrinkage, constructing a three-dimensional network structure, providing good conductive channels, compatibility and binding force, so that the conductive, mechanical and other properties of the low-temperature curing conductive paste are significantly enhanced, and the amount of silver powder used in the low-temperature curing conductive paste can be greatly reduced, thereby achieving the effect of reducing costs.
[0065] As a specific implementation method, the staged rolling method is as follows: the front roller gap is reduced from 120μm to 80μm in stages of 20μm, and rolling is performed 1 to 3 times in each stage; the rear roller gap is reduced from 140μm to 100μm in stages of 20μm, and rolling is performed 1 to 3 times in each stage; the front roller gap and the rear roller gap are reduced to 3 to 5μm in stages of 3-20μm, and rolling is performed 3 to 5 times in each stage, and the rotation speed of each stage is 100rpm.
[0066] In addition, it should be noted that the numerical values given in the embodiments of the present invention are as accurate as possible, but those skilled in the art understand that due to unavoidable measurement errors and experimental operation problems, each number should be understood as an approximate number rather than an absolutely accurate value. For example, due to the error of the weighing instrument, the silver content of each embodiment is the silver powder content value after the silver paste is solidified, excluding organic solvents, and it should be understood that it may have an error of ±2% or ±1%.
[0067] The invention also discloses an electronic component, comprising the low-silver content, low-temperature curing conductive paste prepared by the above method, that is, the low-silver content, low-temperature curing conductive paste is used in the production process of the electronic component.
[0068] Embodiment 1:
[0069] Organic conductive agent: prepare a mixed aqueous solution of hydrochloric acid and methyl orange, the concentration of hydrochloric acid is 1 mol / L, add the monomer raw material - aniline into the mixed aqueous solution in proportion, the monomer is added in an amount equal to the molar ratio of hydrochloric acid, the molar ratio of the template agent to the monomer raw material is 1:5, and the monomer is acidified by stirring at 500 rpm to become a protonated salt.
[0070] Then, the oxidizing agent ammonium persulfate was slowly added (1 mL / min) to the above mixed system, and the system was allowed to react at a low temperature of 0 to 5° C. for 8 hours to polymerize and obtain a precipitated product.
[0071] The obtained precipitated product was then washed with deionized water, methanol, acetone, and ether solvents in sequence to remove reaction byproducts and unreacted products, and then vacuum dried at 60° C. for 36 hours to obtain an organic conductive agent powder.
[0072] Then, the organic conductive agent powder was immersed in a 2 mol / L hydrochloric acid solution at a mass ratio of 1 (organic conductive agent): 100 (concentrated acid) to enhance the protonation doping degree, and the conductivity-enhanced polyaniline was obtained by washing and vacuum drying.
[0073] The measurements were carried out by scanning electron microscopy and transmission electron microscopy, such as Figure 2 As shown, the average particle size of the polyaniline nanofibers was measured to be 50-70 nm, and the length was 500-700 nm. At the same time, the conductivity was measured to be 1.15 S / cm.
[0074] Next, the low-silver content low-temperature curing conductive paste is prepared using the organic conductive agent prepared above. First, an organic mixed solvent is prepared from 85 wt% of dimethyl succinate and 15 wt% of a mixed solvent of methyl isobutyl ketone and cyclohexanone, wherein methyl isobutyl ketone and cyclohexanone are added in equal proportions.
[0075] Then, polyurethane and isocyanate are respectively added to the mixed organic solvent, heated at 70°C for 3h to fully dissolve them, and a polyurethane solution and an isocyanate solution with a solid content of 20% are obtained; the two solutions are mixed in a mass ratio of 8:1, i.e., 8 parts by mass of the polyurethane solution and 1 part by mass of the isocyanate solution, to obtain a silver paste adhesive solution.
[0076] Then, the nano organic conductive agent is added to the silver paste adhesive solution, and pre-rolled in a three-axis roller mill to obtain a uniform organic slurry. Then, the silver powder is added to the organic slurry, and stirred to obtain a conductive slurry premix, in which the silver powder content is 50wt% and the organic conductive agent content is 5.0wt%.
[0077] Then the conductive paste premix is rolled in stages until the fineness of the silver paste reaches 3-5μm. Specifically, the staged rolling process: the front roller distance and the rear roller distance are reduced from 120μm and 140μm to 80μm and 100μm respectively in stages of 20μm, and each stage is rolled twice; then the front roller distance and the rear roller distance are reduced in stages of 20μm to 10μm, and each stage is rolled three times, and finally the front and rear roller distances are adjusted to 5μm for 5 times, and the rolling is ended. The speed of each stage is 100rpm.
[0078] Finally, the obtained silver paste was subjected to vacuum stirring and degassing treatment, with a rotation speed of 3000 rpm, stirring for 8 minutes, and a vacuum degree of -98 Kpa, to obtain a low-silver content, low-temperature curing conductive paste. The surface and cross-section scanning electron microscope photos of the low-silver content, low-temperature curing conductive paste after printing and curing are shown in the figure. Figure 4 As shown in the figure, it can be seen that the surface of the screen-printed silver paste is uniform and flat after curing, the thickness of the cured silver paste is about 20 μm, and it has good adhesion to the substrate.
[0079] In addition, Example 2 and Example 3 were also carried out. The difference between these two examples and Example 1 is that the added amounts of silver paste adhesive, silver powder and organic conductive agent are different (see Table 1 for details), and the other preparation conditions are consistent with Example 1.
[0080] Table 1 Example formulation and performance test results
[0081]
[0082]
[0083] Embodiment 4:
[0084] Organic conductive agent: prepare a mixed aqueous solution of hydrochloric acid and polyvinyl pyrrolidone, the concentration of hydrochloric acid is 1 mol / L, add pyrrole monomer raw material into the mixed aqueous solution in proportion, the monomer is added in an amount equal to the molar ratio of hydrochloric acid, the molar ratio of template agent to monomer raw material is 1:5, and after stirring at 500 rpm, the monomer is acidified to become a protonated salt.
[0085] Then, the oxidant ferric chloride was slowly added into the above mixed system (0.8 mL / min), and the mixture was allowed to react at a low temperature of 0-5° C. for 8 h to obtain a precipitated product by polymerization.
[0086] The obtained precipitated product was then washed with deionized water, methanol, acetone, and ether solvents in sequence to remove reaction byproducts and unreacted products, and then vacuum dried at 60° C. for 36 hours to obtain an organic conductive agent powder.
[0087] Then, the organic conductive agent powder is immersed in a 2 mol / L nitric acid solution according to a mass ratio of the organic conductive agent to concentrated acid of 1:100 to enhance the protonation doping degree, and the conductivity-enhanced nano-organic conductive agent polypyrrole is obtained by washing and vacuum drying.
[0088] Preparation of low silver content low temperature curing conductive paste:
[0089] Firstly, a silver paste organic solvent is prepared by mixing 85 wt % of dimethyl succinate and 15 wt % of a mixed solvent of methyl isobutyl ketone and cyclohexanone, wherein methyl isobutyl ketone and cyclohexanone are added in equal proportions.
[0090] Then, polyurethane and isocyanate are added to the mixed organic solvent respectively, and heated at 80° C. for 3 hours to fully dissolve them, thereby obtaining a polyurethane solution and an isocyanate solution with a solid content of 15%; the two solutions are mixed in a mass ratio of 8:1, i.e., 8 parts by mass of the polyurethane solution and 1 part by mass of the isocyanate solution, to obtain a silver paste adhesive solution.
[0091] Then, the nano organic conductive agent polypyrrole is added to the silver paste adhesive solution, and pre-rolled in a three-axis roller mill to obtain a uniform organic paste. Then, silver powder is added to the organic paste, and stirred to obtain a conductive paste premix, in which the silver powder content is 50wt% and the organic conductive agent content is 0.1wt%.
[0092] Then the conductive paste premix is rolled in stages until the fineness of the silver paste reaches 3-5μm. The staged rolling process: the front roller distance and the rear roller distance are reduced from 120μm and 140μm to 80μm and 100μm respectively in stages of 20μm, and each stage is rolled twice; then it is reduced in stages of 20μm to the front roller distance and the rear roller distance are both 20μm, and each stage is rolled three times. Finally, the front and rear roller distances are adjusted to 10μm and 5μm, and rolled five times each, and the rolling is ended. The rotation speed of each stage is 100rpm.
[0093] Finally, the obtained silver paste was subjected to vacuum stirring and degassing treatment at a rotation speed of 2500 rpm, stirring for 10 min, and a vacuum degree of -98 Kpa to obtain a low-silver content, low-temperature curing conductive paste.
[0094] In the present invention, the conductive performance of the low-silver content and low-temperature curing conductive paste in the above Examples 1-4 was tested: a flexible circuit was printed on a polyimide film by screen printing, and cured in an oven at 150° C. for 30 minutes to obtain a cured silver paste conductor. Figure 5 As shown, in Figure 5 The upper middle part is the actual picture of the silver paste wire, and the lower middle part is the design picture of the silver paste wire. The conductivity test conditions are room temperature 25℃, humidity 25%, the thickness of the silver paste wire is 8-10μm, and the resistivity test is carried out using the RTS-9 dual-electricity four-probe instrument. The test results are shown in Table 1.
[0095] In addition, the silver paste hardness and adhesion test was also conducted: using a pencil hardness tester, the hardness test range was from the softest 6B to the hardest 6H, the silver paste was printed into a 2cm×2cm square, and after curing, it was placed on the glass plate test surface. The test sample was prepared according to the provisions of ISOR1514 and ISOR2828, and the 600-HC33 tape produced by 3M Company of the United States was used to stick on the entire grid, and then torn off at the minimum angle. The ratio of the surface area covered by the glue was obtained, and the test results are shown in Table 1.
[0096] At the same time, the present invention also carried out a reference ratio experiment and performance measurement as shown in Table 1. The experimental parameters and measurement results are shown in Table 1.
[0097] As can be seen from Table 1, from the test results of Examples 1 and 2, when the content of polyaniline, an organic conductive agent, is added at 0.1wt%, the silver content increases and the conductivity rises. From the test results of the reference example and Example 2, it can be seen that the addition of polyaniline, an organic conductive agent, significantly increases the conductivity of the silver paste. From the test results of Examples 2 and 3, it can be seen that when the content of polyaniline is increased from 0.1wt% to 5.0wt%, the conductivity of the silver paste decreases.
[0098] It can be seen from the test results of Examples 3 and 4 that the conductivity of silver paste also decreases under the condition of higher conductive agent content and lower solid content of adhesive liquid. According to the principle of percolation conduction, when the amount of conductive filler exceeds the threshold, it is not advisable to add more conductive filler to further improve the conductivity, which is also not conducive to reducing costs and maintaining rheological properties. The organic conductive agent polyaniline itself has conductivity. After being added to the low-temperature electronic paste, the nano-organic conductive agent fills the gap between the silver powder. During the curing and shrinkage process, it induces a certain microphase separation and self-assembly between the silver powder and the adhesive phase resin, forming a three-dimensional conductive network inside the cured paste, and the conductive path becomes more coherent. At the same time, the resin distribution becomes more robust, so the conductivity and mechanical properties of the paste are greatly improved.
[0099] However, excessive organic conductive agent will expand phase separation, and non-conductive gullies will be formed inside the solidified slurry, resulting in reduced conductivity. Low solid content binder cannot and is not conducive to the formation of a three-dimensional network structure. The test data of the reference examples in Table 1 and Example 2 show that by adding a certain amount of polyaniline and reducing the silver content, the conductive properties of the silver paste can be greatly improved, which can meet the requirements of low-temperature electronic slurry and reduce costs.
Claims
1. A method for preparing a low-silver content, low-temperature curing conductive paste, characterized in that The following steps are involved: Prepare a mixed aqueous solution of hydrochloric acid and methyl orange, the concentration of hydrochloric acid is 1 mol / L, add the monomer raw material - aniline to the mixed aqueous solution in proportion, add the monomer in an amount equal to the molar ratio of hydrochloric acid, the molar ratio of methyl orange to the monomer raw material is 1:5, and after stirring at 500 rpm, the monomer is acidified to become a protonated salt; The oxidant ammonium persulfate was added into the above mixed system at 1 mL / min, and the mixture was allowed to react at a low temperature of 0-5°C for 8 h to polymerize and obtain a precipitated product; The obtained precipitated product was washed with deionized water, methanol, acetone, and ether solvents in sequence to remove reaction byproducts and unreacted products, and then vacuum dried at 60° C. for 36 hours to obtain an organic conductive agent powder; The organic conductive agent powder is immersed in a 2 mol / L hydrochloric acid solution at a mass ratio of 1:100 to enhance the protonation doping degree, and the conductively enhanced polyaniline is obtained by washing and vacuum drying; Adding polyurethane and isocyanate into an organic mixed solvent and fully dissolving them respectively to obtain a polyurethane solution and an isocyanate solution; The polyurethane solution and the isocyanate solution are mixed in a predetermined ratio to obtain a silver paste adhesive solution; Adding the conductive polyaniline to the silver paste adhesive solution, and pre-rolling to obtain an organic slurry; Adding silver powder to the organic slurry and stirring evenly to obtain a conductive slurry premix; wherein the silver content in the conductive slurry premix is 50wt% to 60wt%; Roll-rolling the silver paste premix until the silver paste fineness is 3-5µm; wherein the rolling is a staged rolling method; The silver paste after rolling is subjected to vacuum stirring and degassing treatment to obtain a low-silver content low-temperature curing conductive paste; The content of the organic conductive agent in the conductive paste premix is 0.1 wt% to 5.0 wt%.
2. The method for preparing a low-silver content, low-temperature curing conductive paste according to claim 1, characterized in that: The staged rolling method is: The front roller distance is reduced from 120µm to 80µm in 20µm steps, with 1 to 3 rolls in each step; The back roller spacing is reduced from 140µm to 100µm in 20µm steps, with 1 to 3 rolls in each step; The front and rear roller gaps are reduced to 3~5µm in stages from 3-20µm, with 3~5 rolls in each stage and the rotation speed in each stage is 100 rpm.
3. An electronic component, characterized in that: The present invention comprises a low-silver content and low-temperature curing conductive paste prepared by any one of the methods of claims 1-2.
Citation Information
Patent Citations
Preparation method of hollow quadrangular electro-conductive polypyrrole
CN109851783A